Dosimetric and hematological toxicity analyses of bone marrow‐sparing intensity‐modulated radiation therapy for patients with cervical cancer treated with extended‐field radiation therapy - Jia‐nan Wang; Xi Yu; Li‐na Gu; Dong‐mei Liu; Qiu‐yue Su; Jing‐qi Xia; Wei‐Kang Yun; Xin Li; Xue‐Yuan Hu; Shan‐Shan Yang; De‐Yang Yu (Precision Radiation Oncology)
Abstract Objective This study aimed to assess the dosimetric parameters and hematological toxicity (HT) associated with bone marrow‐sparing (BMS) intensity‐modulated radiation therapy (IMRT) in patients diagnosed with International Federation of Gynecology and Obstetrics (FIGO) stage IIIC cervical cancer undergoing extended‐field radiation therapy (EFRT). Methods Patients with cervical cancer presenting with common iliac or para‐aortic lymph node metastases require EFRT, which often results in grade 3 HT. Therefore, we retrospectively analyzed data of 84 patients with FIGO stage IIIC cervical cancer who underwent concurrent chemoradiotherapy (EFRT, brachytherapy, and weekly cisplatin 40 mg/m2) at Harbin Medical University Cancer Hospital, including 40 who received BMS‐IMRT and 44 who received normal IMRT. Dose–volume histogram (DVH) parameters and estimated treatment times were compared. We also compared acute HT between the normal and BMS groups. Results Dosimetric analysis demonstrated that BMS‐IMRT significantly reduced the mean volume of bone marrow receiving ≥10, ≥20, ≥30, and ≥40 Gy without affecting the target coverage of planning target volume and sparing the organs at risk. Within the BMS‐IMRT group, 37.5% of the patients developed grade ≥3 HT, with an increase in HT (HT3+ = 61.4%) in patients receiving normal‐IMRT (P = 0.029). Conclusions For patients with cervical cancer treated with EFRT, BMS‐IMRT represents a feasible treatment approach that may mitigate HT and facilitate the uninterrupted administration of concurrent chemoradiotherapy.